Tradisi Pemanfaatan Tumbuhan sebagai Jamu Tradisional Pascamelahirkan di Kampung Sindangreret, Cibiru Bandung - Fathin Dhiya Amani; Tri Cahyanto (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study identifies nine plant species used as herbal remedies for postpartum recovery by young mothers in Sindangreret, Bandung. The UV (Use Value) for each plant varies, reflecting their relative importance in traditional practices. Curcuma longa exhibits the highest UV (0.58), highlighting its frequent use and perceived significance in traditional formulations for wound healing, reducing inflammation, and overall health enhancement. Other notable plants include Zingiber officinale (UV 0.51) for anti-inflammatory and energy-boosting properties, and Kaempferia galanga (UV 0.29) for pain relief and stamina enhancement. Traditional usage of these plants is supported by their bioactive compounds and therapeutic potential. The study underscores the importance of preserving ethnobotanical knowledge and suggests further scientific validation and public education to optimize the benefits of these herbal remedies.